Self-Determination Right of Indigenous Peoples - R. S. Garipov (Московский журнал международного права, 2010)
Self-Determination Right is still an object of dispute among international jurists. It often becomes a stumbling block and leads to inter-ethnic conflicts. There are two aspects of the Self-Determination Right: internal and external Self-Determination. According to International Law Indigenous Peoples don’t have the Right to external Self-Determination, but they have internal one which may be realized in the form of Autonomy. Indigenous Peoples may realize their Right to Self-Determination considering the Sovereignty and Territorial Integrity of the State. Nevertheless there is necessity to specify the Self-Determination Right of Indigenous Peoples, its content and realization limits of this Right.